Insertion Specificity of the hATx-6 Transposase of Hydra magnipapillata - Riggs, Paul; Blundell-Hunter, George; Hagelberger, Joanna; Ren, Guoping; Ettwiller, Laurence; Berkmen, Mehmet (Frontiers in Molecular Biosciences, 2021)
Transposable elements (TE) are mobile genetic elements, present in all domains of life. They commonly encode a single transposase enzyme, that performs the excision and reintegration reactions, and these enzymes have been used in mutagenesis and creation of next-generation sequencing libraries. All transposases have some bias in the DNA sequence they bind to when reintegrating the TE DNA. We sought to identify a transposase that showed minimal sequence bias and could be produced recombinantly, using information from the literature and a novel bioinformatic analysis, resulting in the selection of the hATx-6 transposase from Hydra vulgaris (aka Hydra magnipapillata) for further study. This transposase was tested and shown to be active both in vitro and in vivo, and we were able to demonstrate very low sequence bias in its integration preference. This transposase could be an excellent candidate for use in biotechnology, such as the creation of next-generation sequencing libraries.